Evaluating the serial mediating role of job satisfaction and self-efficacy in the relationship between work-family conflict and turnover intention of Portuguese employees - Rosa Lutete Geremias; Lia Cavaco; Ana Maria Sotomayor (Administrative Sciences, 2025)
Previous studies conducted in Portugal on work-family conflict and turnover intention have focused on analyzing how difficulties in balancing employees' work and personal lives affect individual commitment and performance, and little attention has been paid to analyzing factors that may reduce turnover intentions. Therefore, the present study fills a relevant gap in the literature by analyzing other factors that influence turnover intention. This study aimed to analyze the direct and indirect relationship between work-family conflict and turnover intention, with job satisfaction and self-efficacy mediating this relationship. The sample included 277 employees from different sectors in Portugal. The results confirmed that work-family conflict is positively related to turnover intention and that job satisfaction and self-efficacy serially mediate the relationship between work-family conflict and turnover intention. These results suggest that managers should consider analyzing workloads while improving well-being at work so that employees can pay attention to some aspects of their personal lives to reduce work-family conflict and turnover intentions. In addition, the results emphasize the importance of promoting self-efficacy through the continuous design of training plans for better guidance and coordination in the execution of tasks.
Keywords: 350; job satisfaction; self-efficacy; turnover intention; work-family conflict